2010
DOI: 10.4103/2152-7806.69379
|View full text |Cite
|
Sign up to set email alerts
|

Bizarre depressed skull fracture by a tile fragment in a young child, causing superior sagittal sinus injury

Abstract: Background:Head injuries following fall from height are not very uncommon in developing countries due to a lack of safety standards. We describe this bizarre injury by a tile fragment penetrating the superior sagittal sinus (SSS) and its successful surgical management.Case Description:A 7-year-old child presented with a tile fragment embedded in the skull, penetrating SSS. Urgent exploration and removal of the foreign body was done to prevent complications like infection and delayed development of intracranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Several authors have reported on penetrating injury to major intracranial vascular structures such as the basilar artery 3 and superior sagittal sinus. 11,12 Mathew and Sharma 11 reported on a shard of tile penetrating the anterior third of the sagittal sinus, which was able to be extracted with minimal blood loss after simple pressure on the sinus in a 7-year-old child. Sani and colleagues 12 report on an ingenious method of inserting a ''plug'' of temporalis muscle into the sinus perforation by tying it to the nail, which causes it to be inserted into the defect as the nail is withdrawn, which they accomplished in a 37-year-old man.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have reported on penetrating injury to major intracranial vascular structures such as the basilar artery 3 and superior sagittal sinus. 11,12 Mathew and Sharma 11 reported on a shard of tile penetrating the anterior third of the sagittal sinus, which was able to be extracted with minimal blood loss after simple pressure on the sinus in a 7-year-old child. Sani and colleagues 12 report on an ingenious method of inserting a ''plug'' of temporalis muscle into the sinus perforation by tying it to the nail, which causes it to be inserted into the defect as the nail is withdrawn, which they accomplished in a 37-year-old man.…”
Section: Discussionmentioning
confidence: 98%
“…Surgical management of intracranial foreign bodies is not straightforward and must be assessed on a caseby-case basis (16,17). The standard management of penetrating intracranial injury is to fully assess the depth and location of the penetrating object with imaging, followed by a decision whether surgery is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…: 0000-0002-8530-7145 management, for example: venous sinus stenosis leading to venous hypertension and increased intracranial pressure (3,4,6,7,(18)(19)(20), sinus thrombosis leading to late deterioration (11), benign intracranial hypertension (3,6,7,20), and even hemorrhagic infarction (13).…”
Section: Mohamed Mostafa Azizmentioning
confidence: 99%
“…Depressed calvarial fractures overlying the major venous sinus with the absence of a CSF fistula or an associated intracranial hematoma are often managed conservatively because of the associated high risks of major sinus bleeding, especially if a depressed bone fragment has been closing a sinus tear or sinus occlusion and venous infarction (1,11). Elevating depressed skull fractures overlying a cranial venous sinus is hazardous (18).…”
Section: Treatment and Outcomementioning
confidence: 99%
See 1 more Smart Citation